Pengenalan Dan Pelatihan Dasar Robotika Bagi Siswa/Siswi SMK PGRI 01 Semarang - ISYA ARYAN; Budiani Destyningtias; Titik Nurhayati (Gotong Royong, 2025)
The introduction and basic robotics training for vocational high school (SMK) students aims to provide a fundamental understanding of robotics concepts that can be applied in industry and technology. This training combines theoretical knowledge and hands-on practice to develop skills in designing, assembling, and programming simple robots. The curriculum includes an introduction to robot components, control systems, and the programming languages used to control robot movements. Using appropriate tools and devices, students are taught how to assemble robots using robotics kits while understanding basic concepts such as sensors, actuators, and logic programming. By the end of the training, students are expected to have a foundational knowledge of robotics that can be further explored for advanced technology studies and enhance their competitiveness in the industry. This robotics introduction also aims to foster student interest and motivation in the fields of technology and engineering, as well as open career opportunities in the rapidly growing technology sector.